Light trapping and plasmonic enhancement in silicon, dye-sensitized and titania solar cells. (8th January 2016) - Tran, Hong Nhung; Nguyen, Van Hieu; Nguyen, Bich Ha; Vu, Dinh Lam
Abstract: The efficiency of a solar cell depends on both the quality of its semiconductor active layer, as well as on the presence of other dielectric and metallic structural components which improve light trapping and exploit plasmonic enhancement. The purpose of this work is to review the results of recent research on light trapping and plasmonic enhancement in three types of solar cells: thin-film silicon solar cells, dye-sensitized solar cells and solid-state titania solar cells. The results of a study on modeling and the design of light trapping components in solar cells are also presented.